Carbon Nanotubes: Biodegradation of Single‐Walled Carbon Nanotubes by Eosinophil Peroxidase (Small 16/2013). Issue 16 (16th August 2013) - Andón, Fernando T.; Kapralov, Alexandr A.; Yanamala, Naveena; Feng, Weihong; Baygan, Arjang; Chambers, Benedict J.; Hultenby, Kjell; Ye, Fei; Toprak, Muhammet S.; Brandner, Birgit D.; Fornara, Andrea; Klein‐Seetharaman, Judith; et al.
<x xml:space="preserve">Abstract</x> B. Fadeel, V. E. Kagan, and co‐workers report on page 2721 the interaction of one oxidized single‐walled carbon nanotube (SWCNT) with two molecules of eosinophil peroxidase (EPO), one of the major human oxidant generating enzymes. Their study demonstrates that human EPO (in vitro) and murine EPO of ex vivo activated eosinophils catalyses the oxidative biodegradation of SWCNTs. Molecular modeling studies reveal two binding sites for SWCNTs on EPO, one located at the same side as the catalytic site and the other on the distal side of EPO. Eosinophils are key players of the innate immune system and these results are relevant to potential respiratory exposures to carbon nanotubes. Image courtesy of Dr. L. Szekely, Karolinska Institute, Stockholm. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>